"I look deep into this stuff because it's a part of me": Toward a critically relevant civics education. (2nd April 2020) - Clay, Kevin L.; Rubin, Beth C.
ABSTRACT: In communities historically shaped by processes of de jure and de facto segregation; police repression; and lack of access to equitable housing, jobs, and labor-rights, young people find very little of this content reflected in their school-based learning. These societal "civics lessons" indicate the need to move beyond the aim of closing the "civic opportunity gap" and toward a more relevant, critical—even transgressive—approach to civic learning in school. In this article, the authors look across their individual studies to consider how young people of color experienced and interpreted current forms of racialized injustice, how their school-based civic instruction intersected with these experiences, and where they turned to explore these dilemmas. Findings reveal that youth engaged with various out-of-school resources, including family members and new media platforms, to investigate and interpret racialized injustice. Through these findings we developed a grounded theory of school-based civics education that we call critically relevant civics, an approach that embraces the out-of-school resources that young people tap into to navigate the civic world and grapple with the precarious nature of their citizenship status.